The Influence of Work Discipline on the Performance of State Civil Apparatus (ASN) at the Secretariat of the DPRD Banten Province - Djaka Adiwinata; Sucihati Sucihati; Irawan Irawan; Yulaikah Yulaikah; Suhroji Adha (Peneliti.net, 2020)
This study aims to analyze the relationship between work discipline and the performance of the State Civil Apparatus. The method used in this research is a survey method, the form of this research is descriptive quantitative. The sampling method is saturated sample in this research is 98 respondents. The data collection method used a questionnaire and documentation study. The analysis technique uses simple linear regression analysis. The results of this study indicate that work discipline has a positive and significant effect on the performance of the State Civil Service Apparatus.